Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis - Acevedo, Melissa J.; Straehler-Pohl, Ilka; Morandini, Andre C.; Stampar, Sergio N. [UNESP]; Bentlage, Bastian; Matsumoto, George; Yanagihara, Angel; Toshino, Sho; Bordehore, Cesar; Fuentes, Veronica L. (Magnolia Press, 2019)
While records of Carybdea marsupialis in the literature suggest a worldwide distribution of this species, the validity of some of these records has been questioned recently, as has the validity of some nominal Carybdea species. We inspected material of all known species of Carybdea from multiple locations (i.e. Spain, Algeria, Tunisia, Puerto Rico, California, Hawaii, Australia, South Africa, and Japan) using morphological and genetic tools to differentiate Carybdea species as well as understand their evolutionary relationships. We observed morphological differences between adult medusae of Mediterranean and Caribbean C. marsupialis; the most obvious differences were the structure of the phacellae, the structure of the pedalial canal knee bend, and the number and structure of the velarial canals. The characters of the adult Mediterranean specimens agree with the description provided by Claus (1878) for individuals of C. marsupialis from the Adriatic Sea (Italy); specimens from the Caribbean (Puerto Rico) agreed with the description of C. xaymacana by Conant (1897). Significant differences between both species were also observed in the newly released medusa stage. Further, we resolved a discord about the undefined polyp culture originating from Puerto Rico that was long considered Carybdea marsupialis but should be referred to as C. xaymacana. Although C. marsupialis is currently considered the only species of Cubozoa to occur in the Mediterranean, specimens collected in Algeria and Tunisia suggest that species of Alatinidae may also be present in the Mediterranean. Our investigations indicate that Carybdea spp. are more restricted in their geographical distribution than has been recognized historically. These findings confirm that Carybdea arborifera Maas, 1897 from Hawaii, Carybdea branchi, Gershwin & Gibbons, 2009 from South Africa, Carybdea brevipedalia Kishinouye, 1891 from Japan, Carybdea confusa Straehler-Pohl, Matsumoto & Acevedo, 2017 from California, Carybdea marsupialis Linnaeus, 1758 from the European Mediterranean Sea, Carybdea rastonii Haacke, 1886 from South Australia, and Carybdea xaymacana, Conant, 1897 from the Caribbean Sea are valid names representing distinct species, rather than synonyms. A taxonomic key for all valid species is provided, and a neotype for C. marsupialis is designated.
Keywords: box jellyfish; Carybdea murrayana; morphology; identification; cryptic species; geographic distribution; development